Effects of precipitation methods on the properties of protease extracted from starfruit (Averrhoa carambola L.) of different maturity index / Normah Ismail and Ezzana Zuraini Zainuddin - Ismail, Normah; Zainuddin, Ezzana Zuraini (Institute of Research Management and Innovation (IRMI), 2015)
Proteases were extracted from starfruit at maturity Index 2 (unripe, light green) and Index 7 (very ripe, orange) and partially purified using acetone and 40% ammonium sulfate precipitations. Higher yield and proteolytic activity were observed for proteases purified using acetone than 40% ammonium sulfate. As for maturity index, yield and protein concentration of proteases from Index 2 were higher than those from Index 7. SDS-PAGE result showed intense bands for acetone proteases while a distinct band at 50 kDa was observed in all the proteases. Enzyme activity decreased during the seven days storage at 4°C with minimum relative activity of 70%o achieved for acetone proteases at day seven. This study suggested that acetone precipitation is more effective method for purifying starfruit protease based on the yield and proteolytic activity compared to using 40%) ammonium sulphate precipitation. In order to obtain higher protein concentration and proteolytic activity, starfruit at the unripe stage, Index 2 is a better raw material than Index 7 to be used for protease production.